Behavioral Finance: Household Investment and Borrowing Decisions - Pavlo Illiashenko (Visnyk of the National Bank of Ukraine, 2017)
Behavioral finance is still mostly perceived as a field solely devoted to the study of asset pricing and behavior of individual investors. This interpretation to a large extent is misleading as it overlooks a growing body of empirical work in household finance, a subfield of behavioral finance concerned with household investment and borrowing decisions. By focusing on household under-saving, non-participation, and under-diversification, as well as mistakes in choosing debt contracts and managing debt obligations, this paper aims at presenting recent findings in household finance to a wide audience. This review differs from the existent ones as it focuses on the plurality of non-mutually exclusive explanations of the observed phenomena, including those that come from the competing research traditions. The special emphasis is made on the choice between fixed rate and adjustable rate mortgages, given its significance for macrofinancial stability. The review also discusses the evidence indicating that firms are aware of households’ behavioral weaknesses and readily exploit them.